TICE and Their Role in Achieving the Objectives of Morocco’s Strategic Vision 2015-2030 - MOUMEN, Aziz; MAZOUAK ABDERRAZZAK (International Journal of Scientific Research and Innovative Studies, 2024)
The integration of Technologies de l'Information et de la Communication pour l'Éducation (TICE) is a key component of Morocco’s Strategic Vision 2015-2030, which seeks to overhaul the educational landscape and equip students with the necessary skills for a rapidly changing, technology-driven world. As part of this vision, TICE serve as powerful tools to enhance the quality of education, bridge the digital divide, and provide equal opportunities for all students, regardless of their socio-economic background. This article explores the role of TICE in the context of Morocco's educational reforms, examining how these technologies align with the goals of the Vision 2015-2030 and contribute to its success. Specifically, we discuss how TICE are used to improve access to education, promote inclusivity, enhance teaching and learning methods, and support continuous professional development for educators. Despite the challenges of infrastructure gaps, inadequate digital skills among teachers, and financial constraints, TICE have the potential to be a game-changer for Morocco’s education system, supporting the nation’s ambition to become a regional leader in education and innovation. This article also provides recommendations for accelerating the implementation of TICE as part of Morocco's long-term educational strategy. Keywords: TICE, Vision 2015-2030, Morocco, educational reform, digital education, equity in education, teacher development, inclusive education, digital tools, technology in education. Received Date: July 07, 2024 Accepted Date: July 28, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/213